Unlocking cassava brown streak deisease resistance in cassava: insights from genetic variability and combining ability - Sichalwe, K.; Kayondo, S.I.; Edema, R.; Omari, M.; Kulembeka, H.; Rubaihayo, P.; Kanju, E. (MDPI, 2024)
Cassava brown streak disease (CBSD) threatens cassava production in sub-Saharan Africa despite the availability of resistant varieties. Extreme environmental factors weaken plant defenses, reducing CBSD resistance. This study examined CBSD inheritance in cassava populations, assessed genetic variability, and identified superior sources of resistance using F1, S1, and half-sib offspring populations derived from resistant sources. The offspring underwent field evaluation at two distinct sites from 2019 to 2021, and the symptom-free genotypes were analyzed using reverse transcription-quantitative polymerase chain reaction (RT-qPCR). Resistance to CBSD was categorized as most resistant, resistant, most tolerant, or tolerant based on symptoms and virus titers. The findings indicated that the resistance to CBSD is highly influenced by genotypes, F1/S1 types, and environmental conditions. An analysis of combining abilities revealed significant general combining abilities (GCAs) for CBSD, cassava mosaic disease (CMD), and traits associated with yield. The heritability estimates for resistance to CBSD varied between 43.4% and 63.2% for foliar symptoms and 14.6% and 57.9% for root necrosis across locations. The inheritance pattern involved a combination of additive and recessive genes with selfed (S1) populations displaying stronger and more effective resistance to the disease. The cassava brown streak virus (CBSV) was highly prevalent, and the Ugandan cassava brown streak virus (UCBSV) was not prevalent. Four genotypes were highly resistant to CBSD and could be key sources of resistance to this disease.